(untitled) (Acta Scientiarum. Animal Sciences, 2018)
Commercial breed has taken over the Algerian poultry production market which participated in the weakening of the village poultry farming, highly dominant prior to the 1980s. Fortunately, the dietary preferences of consumers, strongly participated in the preservation of the local animal breed diversity. In this context, the aim of this work was to study the growth performances and meat quality of 3 local chicken phenotypes versus commercial broiler chicken in the same breeding conditions in the region of Chlef in Algeria. A week after hatching, 4 randomly chosen samples of 30 chicks from each phenotype normal plumage free-range chicken (NPFRC), crested free-range chicken (CFRC), feathered tarsus free-range chicken (FTFRC) and commercial broiler chicken (CBC) were reared from the age of 1st until 8th week (slaughter age). The three local breed (FTFRC, CFRC and NPFRC) had the comparable body weight, but low (p < 0.05) to those of CBC. In terms of meat quality, the principal components analysis (PCA) and the analysis of variance showed that the free-range chickens were more interesting than the commercial broiler chicken very fat, especially the crested phenotype (CFRC), due to its very high protein 24.6% and very low fat content 1.20%.